Budaya Berkumpul Pada Upacara Ngaben Masa Pandemi Covid-19 Di Buleleng Bali - Bukian, Putu Agus Windu Yasa; Jayanti, Ni Ketut (Metta : Jurnal Ilmu Multidisiplin, 2021)
The implementation of Ngaben is one of the Balinese Hindu traditions for the ceremony of a death. The implementation of Ngaben is a ceremony with a series of many activities and invites a crowd of people. The COVID-19 pandemic period requires people not to carry out gathering activities so that they do not become the cause of the spread of the virus and how to keep ceremonial activities running without reducing meaning. The purpose of this study is to qualitatively identify the culture of gathering during cremation and the solutions offered so that gathering activities do not occur and become the spread of covid-19. This study used a qualitative method through a phenomenological approach, using 4 participants (people who are directly related to religious activities, including the community, community leaders namely head of the ward, 1 participant is a religious leader from the Indonesian Hindu Dharma Association in the Buleleng area). Sampling with nonprobability sampling and using purposive sampling. The results of the study found that there were 3 major themes that were found (1) Ngaben is local wisdom or as a very rigid culture, (2) Ngaben as a form of spreading covid and forming a covid cluster, (3) Changes in Ngaben cultural behavior from conventional to Crematorium. The conclusion is that the community cannot stop cremation activities because it is local wisdom, so to prevent new clusters of covid at the cremation ceremony, the community is required to change their behavior and slowly change the cremation that can be done in the crematorium.